2013
DOI: 10.1111/jocn.12072
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nurse–patient interaction on anxiety and depression in cognitively intact nursing home patients

Abstract: Nurse-patient interaction is an essential factor of quality of care, perceived by long-term nursing home patients. Facilitating nurses' communicating and interactive skills and competence might prevent and decrease depression and anxiety among cognitively intact nursing home patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 100 publications
6
79
0
7
Order By: Relevance
“…We find support for our findings in Haugan’s studies that show the effect of the interaction between nursing home staff and older persons and meaning in life [15,16]. It prevents despair and meaninglessness [14], and has a significant affect on nursing home patients’ depression and anxiety [48]. To have the reciprocal relationship and their interactions become an opportunity and a solution, staff must understand their own values and balance their power in the relationship.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…We find support for our findings in Haugan’s studies that show the effect of the interaction between nursing home staff and older persons and meaning in life [15,16]. It prevents despair and meaninglessness [14], and has a significant affect on nursing home patients’ depression and anxiety [48]. To have the reciprocal relationship and their interactions become an opportunity and a solution, staff must understand their own values and balance their power in the relationship.…”
Section: Resultssupporting
confidence: 87%
“…The interaction between the nurse and the older person and activities in nursing homes can increase mental, physical and psycho spiritual well-being, and prevent despair and meaninglessness [14]. Furthermore, the interaction between the nurse and the older person significantly affects nursing home patients’ depression and anxiety [48]. …”
Section: Discussionmentioning
confidence: 99%
“…A review of 182 studies concluded that anxiety is highly related to depression (Wolitzky-Taylor et al, 2010). In Haugan, Innstrand, and Moksnes (2013) study, a significant association between anxiety and depression (p< 0.05) was found in 202 nursing home residents in Norway who were cognitively intact.…”
Section: The Significant Relationship Between Loneliness Anxiety Andmentioning
confidence: 95%
“…For example, low feelings of connectedness were related to loneliness among 40 older people who were housebound (Han & Richardson, 2010). The significance of connectedness to other people has been identified as a vital component in nurse-patient interaction; this was related to a reduction in feelings of anxiety and depression among 202 cognitively intact older people living in a RACF (Haugan et al, 2013).…”
Section: The Use Of a Spiritual Approach To Adaptationmentioning
confidence: 99%
See 1 more Smart Citation